2020
DOI: 10.1073/pnas.1919723117
|View full text |Cite
|
Sign up to set email alerts
|

Radiative absorption enhancements by black carbon controlled by particle-to-particle heterogeneity in composition

Abstract: Black carbon (BC) absorbs solar radiation, leading to a strong but uncertain warming effect on climate. A key challenge in modeling and quantifying BC’s radiative effect on climate is predicting enhancements in light absorption that result from internal mixing between BC and other aerosol components. Modeling and laboratory studies show that BC, when mixed with other aerosol components, absorbs more strongly than pure, uncoated BC; however, some ambient observations suggest more variable and weaker absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 50 publications
5
75
0
Order By: Relevance
“…Liu et al (2015) reported lower enhancement factors (up to 1.5) consistent with Cappa et al (2012). Discrepancies among laboratory and field observations are also due to the heterogeneity of particle ensemble composition (particle-to-particle differences) and the inaccurate assumption of spherical concentric core-shell structure (Fierce et al, 2020). Limited comparability among measurement techniques contributes to the variability of observed BC optical properties as well (Lack et al 2008, Moosmuller et al 2009, Subramanian et al 2007.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Liu et al (2015) reported lower enhancement factors (up to 1.5) consistent with Cappa et al (2012). Discrepancies among laboratory and field observations are also due to the heterogeneity of particle ensemble composition (particle-to-particle differences) and the inaccurate assumption of spherical concentric core-shell structure (Fierce et al, 2020). Limited comparability among measurement techniques contributes to the variability of observed BC optical properties as well (Lack et al 2008, Moosmuller et al 2009, Subramanian et al 2007.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…One of the key questions in the field of aerosol absorption is the relative importance of black and brown carbon. This is particularly important in biomass burning plumes, where BrC is thought to have a strong effect near the source that diminishes with age (Forrister et al, 2015). Our measurements have shown that the AAE 405−655 values in smoke plumes over the southeast Atlantic were always close to 1 (with a mean AAE 405−655 of 1.13), which was consistent between our airborne measurements in 2017 and ground-based measurements taken on Ascension Island the previous year over a similar wavelength range (Zuidema et al, 2018).…”
Section: Physical and Optical Properties Of Highly Aged Biomass Burnimentioning
confidence: 99%
“…Liu et al, 2017), as well as absorption by brown carbon (BrC; e.g. Forrister et al, 2015;Healy et al, 2015). Where BC is encapsulated by non-BC material, the MAC of the soot may increase due to a lensing effect, which is often quantified using the absorption enhancement (E Abs , which refers to the ratio of the absorption of coated BC to that of uncoated BC).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Those coatings on BC will enhance the light absorption of BC through the so-called lensing effect (Lack and Cappa, 2010), which will further enhance the refractive heating of BC (Jacobson, 2001; Peng et al, 2016). Quantifying the light absorption enhancement of BC requires the information of size distribution, mixing state, morphology and chemical compositions (Fierce et al, 2016;Fierce et al, 2020).…”
mentioning
confidence: 99%